Mediterranean fish biodiversity: an updated inventory with focus on the Ligurian and Tyrrhenian seas - Psomadakis, Peter Nick; Giustino, Stefano; Vacchi, Marino (Zootaxa, 2012)
In this paper we update the Mediterranean fish inventory, analyse the biogeographic features of this fauna and provideexhaustive biodiversity data for the Ligurian and Tyrrhenian seas. According to the data available in 2010, the Mediterraneanfish diversity can be summarized as follows: 602 (including sub-species) bony fish species (Osteichthyes), 79 cartilaginous fishspecies (Chondrichthyes) and 3 cyclostomes (Agnatha); making a total of 684 species belonging to 173 families (147Osteichthyes, 24 Chondrichthyes, 2 Agnatha). Most species 403 (58.9%) have an Atlantic origin, 128 (18.7%) species arecosmopolitan, 90 (13.2%) species are Indo-Pacific, and 63 (9.2%) are endemic to the Mediterranean. In the Ligurian Sea,northern Tyrrhenian and southern Tyrrhenian Sea, the richness can be estimated at 454, 426 and 447 species, respectively. Themost speciose families for the Mediterranean as a whole, but also for the three intra-mediterranean areas studied are theGobiidae, Sparidae, Labridae and Blenniidae; whereas Carangidae is a numerically important family mainly at theMediterranean level. The percentage of endemic fishes within the intra-mediterranean areas studied gradually decrease acrosslatitude from the Ligurian Sea (9.4%) to the northern (8.7%) and southern (8.0%) Tyrrhenian Sea. The updated fish inventorycontains 81 Lessepsian and 48 Atlantic immigrant species, which represent 11.8% and 7.0% of the whole Mediterranean fishcommunity, respectively. The Ligurian Sea (3.1%) houses a higher amount of immigrants with respect to the northern (1.6%)and southern (2.7%) Tyrrhenian sectors.Field observations made during this study indicate that both the Ligurian and Tyrrhenian seas are presently subjected toincreasing colonization events by thermophilic species spreading from the southern Mediterranean and to a lesser degree by the arrival of exotic species either of Atlantic or Indo-Pacific origin.